Revue de Littérature Comparée: tomo 29 (1955), tomo 30 (1956), tomo 31 (1957), tomo 32 (1958). - A., T. (El Colegio de México, 1971)
Se reseñó: Revue de Littérature Comparée: tomo 29 (1955), tomo 30 (1956), tomo 31 (1957), tomo 32 (1958).